The Relationship between Self Efficacy and Quality of Life of Chronic Kidney Failure Patients - Suwandila, Billy (Jurnal Health Society, 2025)
Introduction: Indonesia is one of the countries in Asia with a high rate of chronic kidney failure. Patients with chronic renal failure who undergo haemodialysis experience a decrease in quality of life. Quality of life is influenced by self-efficacy factors. The purpose of the study was to determine the relationship between self efficacy and the quality of life of patients with chronic renal failure. Method: The type of research used is correlational with a cross sectional approach. The population and sample were all chronic renal failure patients in the Hemodialysis Room at Sayang Hospital, Cianjur Regency as many as 108 respondents using total sampling technique. Data collection techniques using questionnaires. The analysis used was simple linear regression test. Result: The results showed that the average self efficacy of chronic renal failure patients was 72.05 and the average quality of life of chronic renal failure patients was 70.87. The results of the simple linear regression test showed a p-value of 0.000, which means that there is a relationship between self efficacy and the quality of life of patients with chronic renal failure in the Hemodialysis Room of RSUD Sayang Cianjur Regency. Conclusion: The conclusion of the results of the study is that there is a relationship between self efficacy and the quality of life of patients with chronic kidney failure in the Hemodialysis Room of RSUD Sayang Cianjur Regency.